2017
DOI: 10.1039/c6cs00270f
|View full text |Cite
|
Sign up to set email alerts
|

Teichoic acids: synthesis and applications

Abstract: This review describes the developments in the synthesis of teichoic acids (TA) - glycosylated poly(alditolphosphates) - and the application of these fragments in immunological studies. These structurally diverse biopolymers are omnipresent constituents of the Gram-positive bacterial cell wall where they fulfill a variety of vital functions. They have been and continue to be attractive synthetic targets because of their challenging structures and the fact that their microheterogeneity precludes their isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 60 publications
1
43
0
Order By: Relevance
“…Literature searches revealed that similar dimeric units are expressed by A. pleuropneumoniae serotypes 1 ( 35 ) and 4 ( 36 ) and by H. influenzae serotype f ( 37 , 38 ). Moreover, in a multitude of bacterial species, one of the hexoses of these dimeric repeating units is replaced by a glycerol, creating a structure similar to that of WTA type II ( 39 , 40 ) ( Fig. 1b ; see also Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature searches revealed that similar dimeric units are expressed by A. pleuropneumoniae serotypes 1 ( 35 ) and 4 ( 36 ) and by H. influenzae serotype f ( 37 , 38 ). Moreover, in a multitude of bacterial species, one of the hexoses of these dimeric repeating units is replaced by a glycerol, creating a structure similar to that of WTA type II ( 39 , 40 ) ( Fig. 1b ; see also Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the additional signals resulted from the fact that the commercially available CDP-glycerol used in the Cps7D and Cps3D reactions was a racemic mixture containing both sn-glycerol-1-phosphate (C2′ of glycerol has S chirality) and sn-glycerol-3-phosphate (C2′ has R chirality; for nomenclature, see reference 40 ). Clearly, both enantiomers are substrates for the enzymes as shown by the complete consumption of CDP-glycerol in the HPLC assay ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Undecaprenyl phosphate is not only the carrier molecule for lipid II but also is used to translocate wall teichoic acids (WTAs) over the membrane [114]. It is therefore likely that WTA synthesis is also localized in RIFs.…”
Section: Does Daptomycin Form Domains With Fluid Lipid Domains (Rifs)mentioning
confidence: 99%
“…In some Gram-positive bacteria, including B. subtilis 168 as well as in S. epidermidis and S. lugdunenis , both LTA and WTA are glycerophosphate polymers (17,18,27,28). Nevertheless, they are synthesized by distinct routes (9,10,29). Figure 1 summarizes the biosynthesis pathways of WTA and LTA of B. subtilis 168.…”
Section: Introductionmentioning
confidence: 99%